The efficacy and long-term safety of a triple combination of 80 mg telmisartan, 5 mg amlodipine and 12.5 mg hydrochlorothiazide in Japanese patients with essential hypertension: a randomized, double-blind study with open-label extension - Higaki, Jitsuo (Hypertens Res, 2017)
The aim of this study was to compare 80 mg telmisartan/5 mg amlodipine/12.5 mg hydrochlorothiazide (T80/A5/H12.5) with 80 mg telmisartan/12.5 mg hydrochlorothiazide (T80/H12.5) to determine their relative blood pressure (BP) lowering effects in essential hypertensive patients with inadequate control and to evaluate the long-term safety of T80/A5/H12.5 in a 52-week extension period. Patients (n=132) were randomly assigned to receive double-blind treatment with T80/A5/H12.5 or T80/H12.5 for 8 weeks after a 6-week run-in-period of T80/H12.5. All 126 patients who completed the double-blind period entered the 52-week open-label extension and received T80/A5/H12.5. The adjusted mean changes from the reference baseline of the trough-seated systolic and diastolic BP (SBP/DBP) at week 8 were significantly larger in the T80/A5/H12.5 group (−10.6/−8.8 mm Hg) than in the T80/H12.5 group (−2.3/−1.3 mm Hg) (P<0.0001). The BP-lowering effect of T80/A5/H12.5 was maintained over the 52-week extension period. The adverse events (AEs) during both treatment periods were generally mild. Drug-related AEs were reported in one patient in each group in the double-blind period and in five patients exposed to T80/A5/H12.5 in the double-blind and/or open-label extension period. T80/A5/H12.5 therapy was clinically and statistically superior to T80/H12.5 therapy for the reduction of BP in patients with essential hypertension uncontrolled with T80/H12.5, and its BP-lowering effect was maintained in the long term. T80/A5/H12.5 was generally well-tolerated.